Digital Marketing Communication Model of Healthy Instant Noodles from Lemonilo - Gatot Wijayanto; Achmad Suhendra Hadiwijaya; Leila Mona Ganiem; Mokhammad A'lan Tabaika; Robbi Rahim (Jurnal Komunikasi Profesional, 2023)
Indonesia is a country that has strong instant noodle culture, most of them grows up with either Indomie or Mie Sedaap regardless they’re rich or poor. Most people cannot resist the taste and flavor of instant noodle; hence, instant noodle becomes Indonesia’s high-ranked product. This time, Lemonilo’s Healthy noodles exists with a different value and core compared to the other instant noodle in Indonesia. Lemonilo’s Healthy noodles exists with Sustainable branding that includes diverse health campaign. Lemonilo’s Healthy noodles that healthy instant noodle with good digital content exists in Indonesian Instant Noodle industry.